Short communication: Coconut fiber mats enhance microbial abundance and vegetation establishment on post-eruption degraded land in Mount Batur, Bali, Indonesia - NI KADEK DESY ANDYA DEWI; NI LUH PUTU SULIS DEWI DAMAYANTI; ANAK AGUNG SAGUNG PUTRI RISA ANDRIANI; I GEDE PUTU WIRAWAN (Society for Indonesian Biodiversity, 2026)
Abstract. Dewi NKDA, Damayanti NLPSD, Andriani AASPR, Wirawan IGP. 2026. Short communication: Coconut fiber mats enhance microbial abundance and vegetation establishment on post-eruption degraded in Mount Batur, Bali, Indonesia. Biodiversitas 27 (3): d270330. https://doi.org/10.13057/biodiv/d270330. Degraded land affected by volcanic eruptions requires specific technologies to support revegetation. In the caldera of Mt. Batur, Bali, Indonesia, mats made from coconut fiber adapted from technology developed by Takino Filter Inc., Japan, were installed on sandy and rocky volcanic substrates to reduce surface soil erosion, limit surface runoff, retain organic matter, increase soil water retention capacity, and create favorable conditions for plant growth. This study aims to evaluate the impact of coconut fiber mats on soil microorganisms, arbuscular mycorrhizal fungus (AMF) and vegetation development in young volcanic soil. This study used exploratory comparative field observation due to limited replications. Soil microorganism abundance, AMF presence, and vegetation development were evaluated using microbiological, mycorrhizal, and molecular approaches. The results showed that the culturable soil microorganisms on PDA increased significantly under coconut fiber mats, reaching 7,976±16.88 CFU g⁻¹, which was much higher than in control plots without mats, which recorded 10.00±2.00 CFU g⁻¹. Four AMF genera (Glomus, Gigaspora, Acaulospora, and Scutellospora) were identified in soil under coconut fiber mats. Vegetation establishment included Gmelina, Leucaena leucocephala, Edelweiss, and grasses. The findings suggest that coconut fiber mats show promising preliminary evidence for enhancing soil biological recovery and promoting revegetation on degraded volcanic landscapes. This study was an exploratory comparative field observation with limited replication and without baseline data; therefore, the findings should be interpreted as associative evidence.